Associations between gut microbiota and diet composition of three arid-adapted rodent species from the Inner Mongolia grassland - Cha, Muha; Wu, Yunga; Man, Duhu; Yi, Xianfeng (Frontiers in Microbiology, 2025)
Food habits are closely associated with the gut microbiota of herbivorous animals; however, limited knowledge exists regarding the arid-adapted rodents. This study investigates the relationship between gut microbiota and dietary composition to offer a scientific basis for comprehending the ecological adaptation strategies of grassland rodents. Cecal contents of Spermophilus alashanicus, S. dauricus, and Meriones unguiculatus were collected and analyzed by using 16S rRNA amplicon sequencing and DNA metabarcoding techniques to determine the structure of gut microbial communities and dietary composition. The results showed that S. alashanicus presented significantly higher gut microbial richness and diversity than S. dauricus and M. unguiculatus. The dominant gut bacterial genera in S. alashanicus and S. dauricus were similar, suggesting that their common genetic backgrounds might influence the colonization and symbiosis of gut microbiota. The three species consumed both plant-based and animal-based foods but differed in their dietary preferences. S. dauricus displayed a significantly higher diversity of animal-based food consumption compared with the other two species. Correlation analysis between diet and gut microbiota indicated that plant-based foods significantly enhanced the diversity and composition of gut microbiota. In contrast, the consumption of animal-based foods significantly decreased microbial diversity. This finding suggests a potential link between the host’s genetic background, dietary composition, and the gut microbiota.